Learnings, continuities and recognition: Identity construction of Cuban academics in Mexican universities - Rodríguez-Alemañy, Daylen; Izquierdo, Isabel (Education Policy Analysis Archives, 2020)
The article shows the results of an investigation of Cuban academics in Mexican institutions of higher education. Our objective was to understand the construction of their identities as Cuban academics, from the meaning of their migration to Mexico. We conducted the study following the biographical method, and through biographical interviews, we rebuilt the life stories of 16 academics, 10 women and six men. The results show the identifications of these academics relating to two moments in their careers: their insertion into the Mexican academy, and the permanence of their positions in the present. The findings highlight the role of socialization in these identity constructions.